2015
DOI: 10.1177/0898010115579769
|View full text |Cite
|
Sign up to set email alerts
|

Tactile Massage as Part of the Caring Act

Abstract: Given the current high-tech health care system with overcrowded units and a shortage of nursing staff, TM could be included as a caring tool to improve the caring in caregiving, allowing nurses to act in aware presence by touch to encourage health and well-being for both the patient and themselves.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 36 publications
0
3
0
1
Order By: Relevance
“…For example, Jensen and colleagues (2012) found that massage therapists reported experiencing reduced anxiety after giving a massage than those who had simply rested for the same period. Airosa et al (2016) reported that the benefit of giving tactile massage was not restricted to patients, or 'receivers', but also extended to the nursing staff, the 'givers'. Similarly, studies that have focused on home-based massage given by lay masseurs have found that the benefits of giving massage include: heightened self-efficacy (Kempson and Conley, 2009); enhanced confidence and satisfaction (Collinge et al, 2013) and the promotion of a sense of closeness (Forchuk et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Jensen and colleagues (2012) found that massage therapists reported experiencing reduced anxiety after giving a massage than those who had simply rested for the same period. Airosa et al (2016) reported that the benefit of giving tactile massage was not restricted to patients, or 'receivers', but also extended to the nursing staff, the 'givers'. Similarly, studies that have focused on home-based massage given by lay masseurs have found that the benefits of giving massage include: heightened self-efficacy (Kempson and Conley, 2009); enhanced confidence and satisfaction (Collinge et al, 2013) and the promotion of a sense of closeness (Forchuk et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Massage therapy was effective in blood pressure, heart rate, respiration rate, and O 2 saturation in patients with congestive heart failure (Jamali, Ramezanli, Jahromi, Zare, & Poorgholami, 2016). Using tactile massage may give nurses a tool in their work, may change their caregiving practice, and may increase their own and their patients' well-being in a stressful environment as the short-term emergency ward (Airosa, Falkenberg, Öhlén, & Arman, 2016). Kübler-Ross (2008) claims that gentle hand pressure is the most effective form of communication with dying patients.…”
Section: Touch In Health Care Practicesmentioning
confidence: 99%
“…Among others, nurses’ main requirements to feel comfortable using touch are the following: a sense of inner balance and the need for supportive environment (Airosa et al, 2016). In fact, even though a number of different aspects influencing positive touch practices are mentioned, a great concern seems to be about affective inner balance (Andersson, Wändell, & Törnkvist, 2007).…”
Section: Touch In Nursingmentioning
confidence: 99%
“…A pouca utilização do toque ou seu uso de forma inadequada pode proporcionar distanciamento entre o paciente e o profissional ( 14), e pode ser resultado do desconhecimento ou do medo do profissional em ser mal interpretado (15), de problemas de autoconhecimento e equilíbrio interno ou de um ambiente com pouca segurança e apoio para sua realização (16)(17).…”
Section: Introductionunclassified